1-Methylcyclopropene retards pak choi (Brassica rapa subsp. chinensis) yellowing via BcNAC055-, BcMYB44-, and BcOBF1-mediated regulation of the key chlorophyll degrading gene BcNYC1 during storage at 20 °C. (30th December 2022) - Song, Liuli; Wang, Junping; Yu, Haitao; Yu, Zhifang
Abstract: The objective of this study was to investigate the molecular regulatory mechanism of 1-methylcyclopropene (1-MCP) treatment on leaf yellowing of pak choi during storage at 20 °C. In the present study, compared with the control and 10 μL/L ethylene-treated pak choi, 5.0 μL/L 1-MCP fumigation alleviated the yellowing process of pak choi as proved by the maintenance of higher levels of colour, chlorophyll content, and appearance. 1-MCP treatment decreased chlorophyll breakdown by downregulating the activity of chlorophyll-degrading enzymes (chlorophyll b reductase (CBR) and pheophytinase (PPH)) and the expression of their related genes ( BcNYC1 and BcPPH ). The application of 1-MCP also inhibited the transcript abundance of ethylene biosynthesis and signal transduction genes ( BcACO, BcEIN3, and BcERF ) and reduced ethylene production, thus helping to maintain the green colour of pak choi; however, ethylene treatment exerted the opposite function. Meanwhile, three transcription factors (BcNAC055, BcMYB44, and BcOBF1) were successfully cloned. Experiments performed using yeast one-hybrid assay, dual-luciferase reporter system and in vivo bioluminescence imaging assay, confirmed that BcNAC055, BcMYB44, and BcOBF1 directly bound to the BcNYC1 promoter. 1-MCP inhibited the expression levels of BcNAC055, BcMYB44, BcOBF1, and BcNYC1 during storage, while the application of ethylene activated their expression. In conclusion, 1-MCP downregulated the expression of the key chlorophyll degradation gene BcNYC1 by inhibiting the transcript level of its three positive regulators (BcNAC055, BcMYB44, and BcOBF1) and lowered the activity of chlorophyll-degrading enzyme CBR, thereby helping mitigate chlorophyll breakdown to retard leaf yellowing in pak choi. The results of this work extend our understanding of 1-MCP-delayed yellowing in postharvest pak choi.